Inside Front Cover. (29th August 2022) - Stirnimann, Guido; Berg, Thomas; Spahr, Laurent; Zeuzem, Stefan; McPherson, Stuart; Lammert, Frank; Storni, Federico; Banz, Vanessa; Babatz, Jana; Vargas, Victor; Geier, Andreas; Engelmann, Cornelius; et al.
Abstract : The cover image is based on the Original Article Final safety and efficacy results from a 106 real‐world patients registry with an ascites‐mobilizing pump by Guido Stirnimann et al., https://doi.org/10.1111/liv.15337 . Image Credit: Sequana Medical NV